2020
DOI: 10.1186/s12889-020-09592-7
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural distinction of potential determinants for prediabetes in Indonesian population aged ≥15 years: a cross-sectional analysis of Indonesian Basic Health Research 2018 among normoglycemic and prediabetic individuals

Abstract: Background Based on Basic Health Research (RISKESDAS) conducted by Ministry of Health, Indonesia, prediabetes prevalence tends to increase from 2007 until 2018. The numbers are relatively higher in rural than those in urban area despite of small discrepancies between the two (~ 2–4%). The purpose of this study was to identify urban-rural differences in potential determinants for prediabetes in Indonesia. Methods This analysis used secondary data collected from nationwide Health Survey in 2018. Respondents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 48 publications
1
22
0
2
Order By: Relevance
“…This study was conducted in full accordance with the World Medical Association Declaration of Helsinki [15]. This was a secondary analysis of data from the Indonesian National Oral Health Survey (INOHS) of 2018 which was part of the Indonesian Basic Health Research (IBHR) [16,17]. The IBHR is a national survey that is conducted every five years and covers all households in Indonesia [16].…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted in full accordance with the World Medical Association Declaration of Helsinki [15]. This was a secondary analysis of data from the Indonesian National Oral Health Survey (INOHS) of 2018 which was part of the Indonesian Basic Health Research (IBHR) [16,17]. The IBHR is a national survey that is conducted every five years and covers all households in Indonesia [16].…”
Section: Methodsmentioning
confidence: 99%
“…Individual blood specimen was taken for laboratory test only in 25,000 households representing the national population. To explore public health answers and inspection procedures, structured interviews were carried out by enumerators who had been trained by the research team (Dany et al, 2020;NIHRD, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Recent study reported that the prevalence of prediabetes in rural and urban Indonesia has reached 44.8% and 34.9% respectively.1³ Interestingly, the risk of prediabetes has already increased starting from the age of 30. 13 In line with this finding, around one-quarter of people with DM in Indonesia are less than 45 years old,2 or commonly grouped as an early onset DM, which is associated with worse outcomes. At the community level, it is urgently needed to start the screening for metabolic diseases in Indonesia at an earlier age.…”
mentioning
confidence: 88%